Implementasi Fungsi Controlling DPD RI terhadap Pemekaran (Studi Pemekaran Kabupaten Musi Rawas Utara) - M. Eza Helyatha Begouvic (Wajah Hukum, 2022)
In the current era of regional autonomy, the word regional expansion has become a familiar word to us. We often hear that word in our daily life, regional expansion is part of decentralization and regional autonomy. Regional expansion is a process of dividing an area into more than one region, with the aim of improving services and accelerating development. Regional expansion is also expected to create regional independence as one of the keys to the success of regional autonomy. The approach in this study is a qualitative research approach (Qualitative Research). This research will be conducted at the Secretariat of the DPD RI Representative of South Sumatra and the Government of North Musirawas Regency which is the object and main focus of researchers in seeing and knowing the concept of the controlling function. To make suggestions regarding the potential for regional expansion, the DPD RI should propose the Maqasid Sharia Theory, so that the expanded regions actually benefit the community.